1998
DOI: 10.1128/cdli.5.5.617-621.1998
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immunoglobulin A Antibodies to Helicobacter pylori in Serum and Gastric Juice in Relation to Mucosal Inflammation

Abstract: Helicobacter pylori is a major etiologic agent in gastroduodenal disorders. In this study, immunoglobulin A (IgA) antibodies to H. pylori antigens were evaluated in serum and gastric juice specimens obtained from patients with gastritis or peptic ulcers by utilizing antibody capture enzyme-linked immunosorbent assays (ACELISAs). Urease α subunit (UA), urease β subunit (UB), the 66-kDa heat shock protein (HSP), and the 25-kDa protein (25K) were used as antigens for the ACELISAs. The antibody titers of the ACELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…We have reported the serum immunoglobulin G immune reaction to H. pylori crude antigens in gerbil models with the early and advanced stages of H. pylori infection [20]. The results with gerbils appear to correlate with results obtained from humans [13,14,23]. The antibody response in-patient with H. pylori infection includes a response to high-molecular proteins (110/120 kDa), medium-size proteins (43-66 kDa) and low-molecular-mass proteins (26,29,30,31 and 33 kDa).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…We have reported the serum immunoglobulin G immune reaction to H. pylori crude antigens in gerbil models with the early and advanced stages of H. pylori infection [20]. The results with gerbils appear to correlate with results obtained from humans [13,14,23]. The antibody response in-patient with H. pylori infection includes a response to high-molecular proteins (110/120 kDa), medium-size proteins (43-66 kDa) and low-molecular-mass proteins (26,29,30,31 and 33 kDa).…”
supporting
confidence: 55%
“…In recent years, serological studies have shown that patients with H. pylori infection develop elevated levels of specific anti-H. pylori antibodies, and several antigens specific for H. pylori have been identified [11][12][13][14][15]. Using serum from the H. pylori -infected Mongolian gerbils model [16,17], which mimics human disease [18,19], we have reported the serum immune response and screened for H. pylori antigens [20] in this model.…”
mentioning
confidence: 99%
“…So far, only a limited number of studies have focused on the local humoral immune response against H. pylori [15][16][17][18][19][20][21][22][23][24][25]. The presence and relevance of locally produced antigastric autoantibodies in H. pylori gastritis have not been investigated.…”
mentioning
confidence: 99%
“…H. pylori seems to bind to gastric epithelial cells and mucin via HSP60 (Huesca et al, 1996), and adaptive immunity to HSP60 was induced in H. pylori-infected patients (Hayashi et al, 1998;Sharma et al, 1997). We reported previously that development of lymphoid tissue in patients with MALT lymphoma was associated with HSP60 (Kobayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%